2010
DOI: 10.1212/wnl.0b013e3181d3e3e9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal cognitive decline is associated with fibrillar amyloid-beta measured by [ 11 C]PiB

Abstract: Objective: To investigate whether longitudinal declines in cognition are associated with higher fibrillar amyloid-beta (A␤) deposition in vivo in individuals without dementia. Method: [11 C]PiB images were obtained to measure fibrillar A␤ burden in 57 participants without dementia from the Baltimore Longitudinal Study of Aging. Participants (33 men, 24 women) had a mean (SD) age of 78.7 (6.2) years. Six participants (4 men, 2 women) had mild cognitive impairment defined as Clinical Dementia Rating ϭ 0.5. To me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
201
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(227 citation statements)
references
References 17 publications
24
201
1
1
Order By: Relevance
“…2 We again found an acceleration of memory decline in preclinical APOE 4 carriers beginning around age 55-60 years, but no similar acceleration of decline on any frontal/executive measure despite the greater amount of fibrillar amyloid in frontal than medial temporal regions. [1][2][3][4][5][6] The frontal/executive measures we used were age-sensitive, surveyed a wide range of relevant skills, and comprised a unique dataset in the extensive literature of cognitive aging. Although none demonstrated significant quadratic effects, several showed significant linear effects (uncorrected for multiple comparisons), particularly mental arithmetic tasks in 4 HMZ, the group with the heaviest frontal amyloid burden.…”
Section: Methods Study Participants From January 1 1994mentioning
confidence: 99%
See 2 more Smart Citations
“…2 We again found an acceleration of memory decline in preclinical APOE 4 carriers beginning around age 55-60 years, but no similar acceleration of decline on any frontal/executive measure despite the greater amount of fibrillar amyloid in frontal than medial temporal regions. [1][2][3][4][5][6] The frontal/executive measures we used were age-sensitive, surveyed a wide range of relevant skills, and comprised a unique dataset in the extensive literature of cognitive aging. Although none demonstrated significant quadratic effects, several showed significant linear effects (uncorrected for multiple comparisons), particularly mental arithmetic tasks in 4 HMZ, the group with the heaviest frontal amyloid burden.…”
Section: Methods Study Participants From January 1 1994mentioning
confidence: 99%
“…[2][3][4][5][6] Yet, in apparent contradiction to the amyloid cascade hypothesis, 7 cortical atrophy is maximal, not in A␤ rich regions, but in medial temporal structures. 5 Another recent challenge to A␤'s posited central role in AD pathogenesis, discussed by others, 5 comes from the clinical underperformance of A␤-modifying therapies including immunotherapy-mediated A␤ clearance that failed to halt the dementia progression.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…[3][4][5][6] Studies using amyloid PET in cognitively normal elderly individuals and individuals with mild cognitive impairment (MCI) and AD dementia have found significant relationships between cognitive deficits and increased brain fibrillar amyloid using both cross-sectional [7][8][9][10][11][12] and longitudinal data [13][14][15][16][17][18][19][20][21][22][23] ; however, other studies have not shown amyloid and cognitive correlations. [24][25][26] In autosomal dominant AD (ADAD), brain amyloid deposition is known to occur 15 years or more before the onset of clinical symptoms, 27,28 and estimated years from expected symptom onset (EYO) calculated from family history data can provide an objective biomarkerindependent estimate of an individual's relative point in the disease process.…”
mentioning
confidence: 99%
“…103 Interestingly, retention of PiB was also observed in elderly subjects without cognitive symptoms, but higher PiB retention at baseline correlated with worse cognitive performance and faster cognitive decline upon follow-up. [108][109][110][111] These studies also showed that despite higher PiB retention, some individuals did not have significant brain atrophy. 112 In addition, PiB-positive patients with MCI had a higher rate of conversion to AD than PiB-negative patients with MCI.…”
Section: Functional Neuroimaging and In Vivo Molecular Imaging (Ab Anmentioning
confidence: 78%